PERCEIVED USEFULNESS, PERCEIVED EASE OF USE, AND PROMOTION IN ENCOURAGING THE DECISION TO USE GOPAY E-WALLET IN PEKANBARU - Bord Nandre Aprila; Sarli Rahman; Verly Novelia; Rizqon Jamil Farhas (Institut Bisnis dan Teknologi Pelita Indonesia, 2024)
The use of e-wallets in Indonesia, including Gopay, continues to increase along with the development of financial technology that facilitates financial transactions. However, a deeper understanding is needed regarding the factors influencing the decision to use e-wallets, particularly in Pekanbaru. This study aims to analyze the influence of perceived usefulness, perceived ease of use, and promotion on the decision to use the Gopay e-wallet. This research employs a survey method using the accidental sampling technique, involving 120 Gopay users. The data collected were analyzed using multiple linear regression. The results show that perceived usefulness, perceived ease of use, and promotion have a positive and significant influence on the decision to use the Gopay e-wallet in Pekanbaru. In conclusion, increasing promotion and developing more user-friendly features can encourage greater e-wallet adoption. These findings provide strategic implications for e-wallet service providers in formulating more effective marketing policies. Penggunaan e-wallet di Indonesia, termasuk Gopay, terus meningkat seiring dengan perkembangan teknologi finansial yang memudahkan transaksi keuangan. Namun, masih diperlukan pemahaman mendalam mengenai faktor-faktor yang memengaruhi keputusan penggunaan e-wallet, khususnya di Kota Pekanbaru. Penelitian ini bertujuan untuk menganalisis pengaruh persepsi manfaat, kemudahan penggunaan, dan promosi terhadap keputusan penggunaan e-wallet Gopay. Penelitian ini menggunakan metode survei dengan teknik accidental sampling, melibatkan 120 responden pengguna Gopay. Data yang diperoleh dianalisis menggunakan regresi linier berganda. Hasil penelitian menunjukkan bahwa persepsi manfaat, perceived usefulness, perceived ease of use, dan promosi memiliki pengaruh positif dan signifikan terhadap keputusan penggunaan e-wallet Gopay di Pekanbaru. Kesimpulannya, peningkatan promosi dan pengembangan fitur yang lebih memudahkan pengguna dapat mendorong peningkatan penggunaan e-wallet. Hasil ini memberikan implikasi strategis bagi perusahaan penyedia layanan e-wallet dalam menyusun kebijakan pemasaran yang lebih efektif.